Development of the Practice Readiness to Evaluate and address Perinatal Depression (PREPD) assessment. (August 2021) - Masters, Grace A.; Brenckle, Linda; Sankaran, Padma; Moore Simas, Tiffany A.; Person, Sharina D.; Allison, Jeroan; Ziedonis, Douglas; Ko, Jean; Robbins, Cheryl; Byatt, Nancy
Highlights: The PREPD quantifies practice readiness to implement perinatal depression interventions. It can be used to tailor interventions to address perinatal depression to practice needs. Practices can also use the PREPD longitudinally and monitor their progress over time. The PREPD helps ensure that practices meet guidelines for addressing maternal mental health. Abstract: Objective: Perinatal depression is a common pregnancy complication and universal screening is recommended. The Practice Readiness to Evaluate and address Perinatal Depression (PREPD) was developed to measure obstetric practice readiness to integrate depression care into workflows. Objectives were to describe: (1) the PREPD; (2) associated characteristics by readiness level; and (3) use of the assessment to measure change. Method: The PREPD has four components, each scored to a 16-point maximum: (1) Environmental Scan (10% of PREPD); (2) Depression Detection, Assessment, and Treatment Questionnaire (30%); (3) Depression-related Policies Questionnaire (10%); and (4) Chart Abstraction (50%). Components were weighted and summed for an overall score. Summary and component scores were calculated by patient, practice, and provider. Results: Average overall PREPD score was 7.3/16 (range: 4.8–9.9); scores varied between practices. The Environmental Scan averaged 2.0/16 (range: 0–5.2); Detection, Assessment, and Treatment averaged 8.3/16 (range: 3.0–11.5); Chart Abstraction averaged 7.2/16 (range: 5.1–9.6); and Depression-related Policies averaged 10.4/16 (range: 7.5–15). Conclusion: We found wide variation in obstetric practices' readiness to implement interventions for depression; most were minimally prepared. These data may be used to tailor practice intervention goals and as benchmarks with which to measure changes in integration of depression care over time.